Biological Synthesis of Silver Nanoparticles Using Hibiscus Sabdariffa Leaf Extract and It’s Antibacterial Sensitivity Assay - Prachi Meshram; Megha Walthare (International Journal of Tropical Medicines, 2024)
In this study, AgNO3 was effectively used to synthesize silver nanoparticles. Hibiscus sabdariffa leaf extract was used to promptly and easily synthesize silver nanoparticles. An UV-Visible spectrophotometer showed absorbance peak in range of 300-600 nm. The procedure was found to be easy to follow, quick, least step and safe for the environment. It is non-toxic, and a viable substitute for traditional physical or chemical procedures. At room temperature, silver ions were converted into silver nanoparticles in about 15 to 20 minutes without the need of any dangerous chemicals. The growing prevalence of antibiotic resistance in bacteria is becoming a significant issue for accurate Infectious illness diagnosis and treatment. Escherichia coli (E. coli), Enterococcus faecalis (E. faecalis), Pseudomonas aeruginosa (P. aeruginosa) and Klebsiella pneumoniae are microbes used for assessment and evaluation of antibacterial sensitivity test against Hibiscus sabdariffa based silver nanoparticles. It is found that gram positive and negative both strains of bacteria affected by the antibacterial qualities of Hibiscus sabdariffa based silver nanoparticles.
Keywords: Hibiscus sabdariffa; Silver nanoparticles; UV–Visible spectroscopy; antimicrobial sensitivity; green synthesis; plant extract